2H nuclear magnetic resonance study of deuterated water dynamics in perfluorosulfonic acid ionomer Nafion. (November 2016) - Han, Jun Hee; Lee, Kyu Won; Lee, Cheol Eui
Abstract: We have employed deuteron nuclear magnetic resonance (NMR) spectroscopy in order to study the dynamics of the deuterated water (D2 O) molecules introduced into a perfluorosulfonic acid ionomer Nafion (NR-211) film. According to the 2 H NMR spectral analysis, the deuterated water molecules at low temperatures occupied either relatively rigid or mobile sites up to the temperature T M =240 K where all the deuterated water molecules became mobile. The temperature-dependent NMR linewidths sensitively reflected the motional narrowing of the rigid and mobile sites, and the NMR chemical shift reflected significant changes in the hydrogen bonds of the deuterated water. While a slow- to fast-limit motional transition was manifested at T M in the laboratory-frame NMR spin–lattice relaxation, the rotating-frame spin–lattice relaxation indicated no bulk liquid water state down to 200 K. Abstract : Highlights: Deuteron NMR spectroscopy to study the deuterated water dynamics in a Nafion (NR-211) film. Deuterated water molecules become fully mobile at TM =240 K. NMR chemical shift reveals marked changes with temperature in the hydrogen bonds of deuterated water. A slow- to fast-limit motional transition at T M in the laboratory-frame NMR spin–lattice relaxation. No bulk liquid water state down to 200 K according to the rotating-frame spin–lattice relaxation.